2014
DOI: 10.1073/pnas.1402858111
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of amphiphilic Janus dendrimers into uniform onion-like dendrimersomes with predictable size and number of bilayers

Abstract: A constitutional isomeric library synthesized by a modular approach has been used to discover six amphiphilic Janus dendrimer primary structures, which self-assemble into uniform onion-like vesicles with predictable dimensions and number of internal bilayers. These vesicles, denoted onion-like dendrimersomes, are assembled by simple injection of a solution of Janus dendrimer in a water-miscible solvent into water or buffer. These dendrimersomes provide mimics of double-bilayer and multibilayer biological membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 49 publications
7
160
0
Order By: Relevance
“…Indeed, for various types of lectins, this surface design has been found to be inert (16,(27)(28)(29). Also, the presence of methoxytriethoxy has previously been shown to be conducive to the formation of onionlike dendrimersomes (3). This result prompted the use of Janus GDs as building blocks for obtaining onion-like GDSs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, for various types of lectins, this surface design has been found to be inert (16,(27)(28)(29). Also, the presence of methoxytriethoxy has previously been shown to be conducive to the formation of onionlike dendrimersomes (3). This result prompted the use of Janus GDs as building blocks for obtaining onion-like GDSs.…”
Section: Resultsmentioning
confidence: 99%
“…Four JDs were selected from 19 libraries containing 144 compounds ( Fig. 2) (9,24,26,36). JD-1, JD-2, and JD-3 are twin-twin molecules (9, 24) containing twin-hydrophobic and twin-hydrophilic dendrons, whereas JD-4 is a single-single compound (26) based on single-hydrophobic and single-hydrophilic dendrons.…”
Section: Significancementioning
confidence: 99%
“…mechanical resistance, wall thickness, chemical groups exposed on the outer surface) has driven the search for new categories of amphiphiles other than phospholipids. [10][11][12] Two examples are represented by polymersomes [13][14][15] and dendrimersomes, [16][17][18][19][20][21][22] which are obtained through the self-assembly of amphiphilic block co-polymers or JDs, respectively. Whereas the potential of polymersomes in biomedical studies has been already demonstrated, 14,15 dendrimersomes have been proposed only very recently, and therefore their behaviour in biological environments is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%